A strong, tough, and osteoconductive hydroxyapatite mineralized polyacrylamide/dextran hydrogel for bone tissue regeneration. (1st April 2019) - Fang, Ju; Li, Pengfei; Lu, Xiong; Fang, Liming; Lü, Xiaoying; Ren, Fuzeng
Graphical abstract: Abstract: The design of hydrogels with adequate mechanical properties and excellent bioactivity, osteoconductivity, and capacity for osseointegration is essential to bone repair and regeneration. However, it is challenging to integrate all these properties into one bone scaffold. Herein, we developed a strong, tough, osteoconductive hydrogel by a facile one-step micellar copolymerization of acrylamide and urethacrylate dextran (Dex-U), followed by the in situ mineralization of hydroxyapatite (HAp) nanocrystals. We show that the soft, flexible, and hydrophobically associated polyacrylamide (PAAm) network is strengthened by the stiff crosslinked Dex-U phase, and that the mineralized HAp simultaneously improves the mechanical properties and osteoconductivity. The obtained HAp mineralized PAAm/Dex-U hydrogel (HAp-PADH) has extremely high compressive strength (6.5 MPa) and enhanced fracture resistance (over 2300 J m −2 ), as compared with pure PAAm hydrogels. In vitro, we show that the mineralized HAp layer promotes the adhesion and proliferation of osteoblasts, and effectively stimulates osteogenic differentiation. Through the in vivo evaluation of hydrogels in a femoral condyle defect rabbit model, we show regeneration of a highly mineralized bone tissue and direct bonding to the HAp-PADH interface. These findings confirm the excellent osteoconductivity and osseointegration ability of fabricated HAp-PADH. The present HAp-PADH, with its superior mechanical properties and excellent osteoconductivity, should have great potential for bone repair and regeneration. Statement of Significance: We developed a strong, tough, and osteoconductive hydrogel by a facile one-step micellar copolymerization of acrylamide and urethane methacrylate dextran (Dex-U), followed by the in situ mineralization of hydroxyapatite (HAp) nanocrystals. The hydrophobic micellar copolymerization and introduction of the stiff crosslinked Dex-U phase endowed the soft polyacrylamide (PAAm) network with enhanced strength and toughness. The in situ mineralized HAp nanocrystals on the hydrogels further improved the mechanical properties of the hydrogels and promoted osteogenic differentiation of cells. Mechanical tests together with in vitro and in vivo evaluations confirmed that the HAp mineralized PAAm/Dex-U hydrogel (HAp-PADH) achieved a combination of superior mechanical properties and excellent osseointegration, and thus may offer a promising candidate for bone repair and regeneration.